End-stage renal disease in autosomal dominant polycystic kidney disease: a comparison of dialysis-related utilization and costs with other chronic kidney diseases - Brunelli SM; Blanchette CM; Claxton AJ; Roy D; Rossetti S; Gutierrez B (Dove Medical Press, 2015)
Steven M Brunelli,1 Christopher M Blanchette,2,3 Ami J Claxton,1 Debosree Roy,2 Sandro Rossetti,3 Benjamin Gutierrez31DaVita Clinical Research, Minneapolis, MN, USA; 2University of North Carolina, Charlotte, NC, USA; 3Otsuka America Pharmaceutical, Inc., Princeton, NJ, USA Background: Autosomal dominant polycystic kidney disease (ADPKD) is the leading inheritable cause of end-stage renal disease (ESRD) and one of the leading causes of ESRD overall. ADPKD patients differ from the overall dialysis population; however, there is little published data regarding health care costs for ADPKD patients on dialysis. Methods: This retrospective observational cohort study was designed to quantify health care utilization and costs for ADPKD patients with ESRD who received initial services at a single large dialysis organization between January 1, 2007 and December 31, 2009. Parallel results and baseline patient characteristics for control patients with ESRD etiologies other than ADPKD were performed for reference. Dialysis-related utilization and health care costs for patients with ADPKD in ESRD overall and during time horizons that correspond to Medicare-eligibility benchmarks were analyzed. Baseline patient characteristics were described for all patients and included demographics, comorbid illnesses, and clinical characteristics. Dialysis-related utilization, hospitalization rates, and health care costs were considered longitudinally. Results: Total health care costs for ADPKD patients were high at US$51,048 per patient-year based on the overall analysis. Total health care costs were lower for ADPKD patients than for control patients on dialysis. Patients with ADPKD were generally younger, had a lower Charlson Comorbidity Index, and had lower rates of comorbid conditions, which may have contributed to the lower overall costs seen for patients with ADPKD. Conclusion: Health care resource utilization and costs for patients with ADPKD in ESRD requiring dialysis were high, and therapeutic interventions that can prevent or delay the progression to ESRD may increase dialysis-free life for patients with ADPKD. Keywords: ADPKD, chronic kidney disease, dialysis, health care costs